2021
DOI: 10.3390/brainsci11050632
|View full text |Cite
|
Sign up to set email alerts
|

The Role of White Matter Disconnection in the Symptoms Relating to the Anarchic Hand Syndrome: A Single Case Study

Abstract: The anarchic hand syndrome refers to an inability to control the movements of one’s own hand, which acts as if it has a will of its own. The symptoms may differ depending on whether the brain lesion is anterior, posterior, callosal or subcortical, but the relative classifications are not conclusive. This study investigates the role of white matter disconnections in a patient whose symptoms are inconsistent with the mapping of the lesion site. A repeated neuropsychological investigation was associated with a re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Typical damaged brain areas include fronto-mesial and anterior cingulate areas as well as the anterior corpus callosum (Feinberg et al, 1992). Anarchic hand syndrome (AHS) is a related disorder, which ensues from a relatively circumscribed lesion of the anterior corpus callosum (Feinberg et al, 1992, but see Pacella et al, 2021 for a more recent account). In this syndrome, the individuals' hands move outside of the volitional control as well (Della Sala, 2009;Jenkinson et al, 2015); however, intermanual conflicts are more typical than utilization behavior.…”
Section: Characteristics and Etiology Of Bidmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical damaged brain areas include fronto-mesial and anterior cingulate areas as well as the anterior corpus callosum (Feinberg et al, 1992). Anarchic hand syndrome (AHS) is a related disorder, which ensues from a relatively circumscribed lesion of the anterior corpus callosum (Feinberg et al, 1992, but see Pacella et al, 2021 for a more recent account). In this syndrome, the individuals' hands move outside of the volitional control as well (Della Sala, 2009;Jenkinson et al, 2015); however, intermanual conflicts are more typical than utilization behavior.…”
Section: Characteristics and Etiology Of Bidmentioning
confidence: 99%
“…hand syndrome Disembodiment of the limb Potential underlying mechanism relating to white matter disconnection and brain lesions (Pacella et al, 2021) Motor control of the affected limb is disinhibited and moves non-volitionally No disownership of the limb -Right inferior parietal lobe (Della Sala, 2009; Jenkinson et al, 2015)-White matter disconnection of antero-posterior, insular, and interhemispheric networks(Pacella et al, 2021) …”
mentioning
confidence: 99%
“…They showed that spatial neglect is associated with disconnection of superior longitudinal fasciculus (SLF) II measured using this indirect approach, and that this result is supported by individual white matter tractography dissection [36]. Pacella et al, [38] also depicted a patient's lesion as a region of interest (ROI), which they overlaid an atlas of white matter tracts created from healthy DWI data to measure the disconnection of the white matter tract of the ROI using Tractotron in the BCB toolkit [35]. The disconnections of white matter tracts such as the SLF, arcuate fasciculus (AF), and inferior longitudinal fasciculus indicated by the indirect approach were also confirmed in subsequent direct analysis using DTI [38].…”
Section: Introductionmentioning
confidence: 95%
“…Pacella et al, [38] also depicted a patient's lesion as a region of interest (ROI), which they overlaid an atlas of white matter tracts created from healthy DWI data to measure the disconnection of the white matter tract of the ROI using Tractotron in the BCB toolkit [35]. The disconnections of white matter tracts such as the SLF, arcuate fasciculus (AF), and inferior longitudinal fasciculus indicated by the indirect approach were also confirmed in subsequent direct analysis using DTI [38]. Furthermore, Wawrzyniak et al, [39] successfully confirmed the wellknown relationship between damage to white matter tracts and symptoms caused by disconnection of specific white matter tracts using voxel-wise disconnection mapping as an indirect approach.…”
Section: Introductionmentioning
confidence: 98%